Efficacy of ketamine for comorbid depression and acute or chronic pain: A systematic review - Aksharra Balachandran; Vanessa K. Tassone; Fathima Adamsahib; Anne-Marie Di Passa; Sarah Kuburi; Ilya Demchenko; Karim S. Ladha; Karim S. Ladha; Venkat Bhat; Venkat Bhat; Venkat Bhat; Venkat Bhat; et al. (Frontiers in Pain Research, 2022)
Pain and depression frequently co-occur. Due to its antidepressant and analgesic properties, ketamine has been used for the management of treatment-resistant depression and pain. This systematic review examined the literature on the efficacy of sub-anesthetic doses of ketamine in individuals experiencing comorbid depression and chronic pain (CDCP), as well as comorbid depression and acute pain (CDAP). A secondary objective was to provide an assessment of dosage, route, and adverse effects of ketamine treatment for CDCP and CDAP. A literature search was conducted on MEDLINE, PsycINFO, and Embase databases, coupled with a manual screening of the bibliography sections of included articles. In addition, registered ongoing and planned trials were searched on Clinicaltrials.gov. The end date of the search was April 9th, 2022. Included studies assessed changes in depression and pain in patients receiving at least one sub-anesthetic dose of ketamine. Assessment of quality was conducted using the GRADE checklist. Of the 7 CDCP clinical trials, 3 reported a reduction in depression and pain, 3 reported a reduction in depression or pain only, and 1 reported no improvement in either comorbidity. Among the 7 CDAP clinical trials, 4 studies found improvements in depression and pain while the remaining 3 reported improvements in only one parameter. Ten of the 12 case studies and 2 of the 3 observational studies assessing CDCP and CDAP found improvements in pain and depression scores post-treatment with effects of variable duration. The planned methodologies of the registered clinical trials are in line with those of the published research. Preliminary evidence supports the efficacy of ketamine in treating CDCP and CDAP. However, the current review identified a small number of heterogeneous studies with mixed results, preventing comprehensive conclusions. More longitudinal placebo-controlled studies are needed to identify the effects of ketamine for patients with CDCP and CDAP.